Evaluation of width and width uniformity of near-field electrospinning printed micro and sub-micrometer lines based on optical image processing. (2nd February 2018) - Zhao, Libo; Xia, Yong; Hebibul, Rahman; Wang, Jiuhong; Zhou, Xiangyang; Hu, Yingjie; Li, Zhikang; Luo, Guoxi; Zhao, Yulong; Jiang, Zhuangde
Abstract: This paper presents an experimental study using image processing to investigate width and width uniformity of sub-micrometer polyethylene oxide (PEO) lines fabricated by near-filed electrospinning (NFES) technique. An adaptive thresholding method was developed to determine the optimal gray values to accurately extract profiles of printed lines from original optical images. And it was proved with good feasibility. The mechanism of the proposed thresholding method was believed to take advantage of statistic property and get rid of halo induced errors. Triangular method and relative standard deviation ( RSD ) were introduced to calculate line width and width uniformity, respectively. Based on these image processing methods, the effects of process parameters including substrate speed ( v ), applied voltage ( U ), nozzle-to-collector distance ( H ), and syringe pump flow rate ( Q ) on width and width uniformity of printed lines were discussed. The research results are helpful to promote the NFES technique for fabricating high resolution micro and sub-micro lines and also helpful to optical image processing at sub-micro level.